Finding a possible biomarker to tackle Parkinson’s disease by splice analysis and random point mutations to counter the expression of genes involved in Parkinson’s disease - Kalwad, Piyusha; Guttapadu, Ranjitha; S, Pradeep (International Journal of Applied Sciences and Biotechnology, 2017)
The genes showing aberrant alternative splicing in Parkinson’s disease namely SNCA, SNCAIP, LRRK2, SRRM2, MAPT and PARK2 were analysed. Two of the genes, namely SNCAIP and SRRM2 that showed high effect were taken and splice site analysis was carried out. Random mutations were carried out on these two genes using Human Splicing Finder tool and the mutations showing the most promising results (i.e., mutations that can restore natural gene expression) were appropriately chosen to tackle Parkinson’s disease. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 336-344